Assessment of altered three‐dimensional blood characteristics in aortic disease by velocity distribution analysis. Issue 3 (23rd September 2014) - Garcia, Julio; Barker, Alex J.; van Ooij, Pim; Schnell, Susanne; Puthumana, Jyothy; Bonow, Robert O.; Collins, Jeremy D.; Carr, James C.; Markl, Michael
<x xml:space="preserve">Abstract</x> Purpose To test the feasibility of velocity distribution analysis for identifying altered three‐dimensional (3D) flow characteristics in patients with aortic disease based on 4D flow MRI volumetric analysis. Methods Forty patients with aortic (Ao) dilation (mid ascending aortic diameter MAA = 40 ± 7 mm, age = 56 ± 17 years, 11 females) underwent cardiovascular MRI. Four groups were retrospectively defined: mild Ao dilation (n = 10; MAA < 35 mm); moderate Ao dilation (n = 10; 35 < MAA < 45 mm); severe Ao dilation (n = 10; MAA > 45 mm); Ao dilation+aortic stenosis AS (n = 10; MAA > 35 mm and peak velocity > 2.5 m/s). The 3D PC‐MR angiograms were computed and used to obtain a 3D segmentation of the aorta which was divided into four segments: root, ascending aorta, arch, descending aorta. Radial chart displays were used to visualize multiple parameters representing segmental changes in the 3D velocity distribution associated with aortic disease. Results Changes in the velocity field and geometry between cohorts resulted in distinct hemodynamic patterns for each aortic segment. Disease progression from mild to Ao dilation + AS resulted in significant differences (P < 0.05) in flow parameters across cohorts and increased radial chart size for root and ascending aorta segments by 146% and 99%, respectively. Conclusion Volumetric 4D velocity distribution analysis has the potential to identify characteristic changes in regional blood flow patterns in patients with aortic disease. Magn Reson Med 74:817–825, 2015. © 2014 Wiley Periodicals, Inc.